Intragastric and Intranasal Administration of Lactobacillus paracasei NCC2461 Modulates Allergic Airway Inflammation in Mice - Céline Pellaton; Sophie Nutten; Anne-Christine Thierry; Caroline Boudousquié; Nathalie Barbier; Carine Blanchard; Blaise Corthésy; Annick Mercenier; François Spertini (Hindawi Limited, 2012)
Introduction. Preclinical and clinical evidences for a role of oral probiotics in the management of allergic diseases are emerging. Aim. We aimed at testing the immunomodulatory effects of intranasal versus intragastric administration of Lactobacillus paracasei NCC2461 in a mouse model of allergic airway inflammation and the specificity of different probiotics by comparing L. paracasei NCC2461 to Lactobacillus plantarum NCC1107. Methods. L. paracasei NCC2461 or L. plantarum NCC1107 strains were administered either intragastrically (NCC2461) or intranasally (NCC2461 or NCC1107) to OVA-sensitized mice challenged with OVA aerosols. Inflammatory cell recruitment into BALF, eotaxin and IL-5 production in the lungs were measured. Results. Intranasal L. paracasei NCC2461 efficiently protected sensitized mice upon exposure to OVA aerosols in a dose-dependent manner as compared to control mice. Inflammatory cell number, eotaxin and IL-5 were significantly reduced in BALF. Intranasal supplementation of L. paracasei NCC2461 was more potent than intragastric application in limiting the allergic response and possibly linked to an increase in T regulatory cells in the lungs. Finally, intranasal L. plantarum NCC1107 reduced total and eosinophilic lung inflammation, but increased neutrophilia and macrophages infiltration. Conclusion. A concerted selection of intervention schedule, doses, and administration routes (intranasal versus intragastric) may markedly contribute to modulate airway inflammation in a probiotic strain-specific manner.